2012
DOI: 10.1093/aob/mcs200
|View full text |Cite
|
Sign up to set email alerts
|

At3g08030 transcript: a molecular marker of seed ageing

Abstract: At3g08030 mRNA detection in a dry seed lot has potential for use as a molecular marker for germination performance in a variety of plant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Much less research has been done regarding stored mRNAs and seed aging. The transcripts of an Arabidopsis gene, At3g08030, and its homologs in two other plant species were found to be present in freshly collected seeds, but reduced or not detected in aged seeds (Garza-Caligaris et al, 2012). The authors suggested that the At3g08030 transcript could be a potential biomarker for seed aging.…”
Section: Degradation Of Stored Mrnas Is Highly Correlated With Aging mentioning
confidence: 99%
“…Much less research has been done regarding stored mRNAs and seed aging. The transcripts of an Arabidopsis gene, At3g08030, and its homologs in two other plant species were found to be present in freshly collected seeds, but reduced or not detected in aged seeds (Garza-Caligaris et al, 2012). The authors suggested that the At3g08030 transcript could be a potential biomarker for seed aging.…”
Section: Degradation Of Stored Mrnas Is Highly Correlated With Aging mentioning
confidence: 99%
“…There are also a number of proteins that are connected by a domain of unknown function (DUF) deeply involved in cell wall metabolism (lower left in Fig. 6) (e.g., Garza-Caligaris et al, 2012;Vazquez-Lobo et al, 2012).…”
Section: Functional Category Comparisons Among the Differentially Rmentioning
confidence: 99%
“…Pre-storage conditions and genotypic effects also play crucial roles in influencing longevity characteristics. Markers of quantitative trait loci (QTL) detected after artificial ageing have been associated with abiotic and biotic stress response genes (Nagel et al 2009) and a range of loci linked to stress response and longevity were identified (Miura et al 2002;Clerkx et al 2004;Garza-Caligaris et al 2012;Nguyen et al 2012). Hence, seed ageing is genotype dependent, but it is poorly understood which factors affect seed response in relation to maternal environment, ageing treatment and genetic background.…”
Section: Introductionmentioning
confidence: 99%